ANALYSIS OF READING QUESTIONS IN ENGLISH FOR HEALTH COURSE BOOK BASED ON REVISED BLOOMâ€™S TAXONOMY THEORY - Meklan Junito (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The objectives of this research are to investigate the types of questions based on Revised Taxonomy Bloom used in reading task on English for health coursebooks and to investigate the dominant type of questions based on Revised Taxonomy Bloom used in reading task on EnglishÂ for health coursebooks. This study used descriptive study which tried to potrait the use of Taxonomy Blooms revise used in English coursebook for nursing students. This research used an English coursebook for nursery students entitled â€œEnglish for Healthâ€ by Eka Susilowati and Agustin Widiani. The instrument of observation was checklist. The observation checklist contains six components of cognitive process of Revised Bloomâ€Ÿs Taxonomy. The researcher gave mark (âˆš) in the columns of the checklist if the task is using the component of cognitive process of Revised Bloomâ€Ÿs Taxonomy. The finding showed that there were four components of cognitive domain were found in English for Health students textbooks, they were remembering, understanding, applying, and analyzing. There were 76 questions related to remembering component, then 14 questions belong to understanding component. Moreover, the rest two questions were included into one question for applying component and one for analyzing component. However, there was no question which belong to evaluating and creating component of cognitive domain in book. To conclude the â€œEnglish for Health course book contained four components of cognitive domain, they were remembering, understanding, applying, and analyzing.Â Keywords : Reading Questions, English for Health, Revised Bloomâ€™s Taxonomy